2013
DOI: 10.1080/03630242.2013.826319
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Determinants of Maternal Health Care Service Utilization in Nigeria

Abstract: Despite the high maternal mortality ratio in Nigeria, the use of maternal health care services is very poor. Attempts to explain this situation has focused on individual level factors and the influence of community contextual factors have not received much attention. This study examined the relation of community factors to the use of antenatal care in Nigeria, and explored whether community factors moderated the association between individual characteristics and antenatal care visits. Data were drawn from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
62
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 14 publications
12
62
1
3
Order By: Relevance
“…A woman's decision-making autonomy was defined as decision making regarding her own health and was determined by whether a woman made decisions alone or jointly with her husband or partner, including if the husband alone or others made decisions for her health care. In previous studies (Ononokpono, Odimegwu, Adedini, & Imasiku, 2013), mass media exposure has been found to be strongly associated with maternal health outcomes. This variable was grouped into three categories: newspaper, radio, and television.…”
Section: Variablesmentioning
confidence: 83%
“…A woman's decision-making autonomy was defined as decision making regarding her own health and was determined by whether a woman made decisions alone or jointly with her husband or partner, including if the husband alone or others made decisions for her health care. In previous studies (Ononokpono, Odimegwu, Adedini, & Imasiku, 2013), mass media exposure has been found to be strongly associated with maternal health outcomes. This variable was grouped into three categories: newspaper, radio, and television.…”
Section: Variablesmentioning
confidence: 83%
“…Harttgen and Misselhorn (15) argued that there would be differences in health outcomes of children from two communities that have contrasting characteristics. Community conditions have been noted to impact on health outcomes of individuals (16) through such levers as physical structures, social structures, and service provisions (17). For instance, children born or raised in communities that lack a health care facility are likely to suffer poorer health outcomes compared to those children from communities where good health facilities are available (18).…”
mentioning
confidence: 99%
“…Our finding that increasing age and parity are associated with less or least adequate care is well established in several studies (Do et al, 2014;Kodzi et al, 2012;Kruk, Rockers, Mbaruku, Paczkowski, & Galea, 2010;Ononokpono, Odimegwu, Imasiku, & Adedini, 2013;Smith, Tawiah, & Badasu, 2012) as these women are likely to assume confidence in themselves for their own maternity needs. This could be evident in environments where cost and access factors (distance/transport) may create a condition of "despair" and lower seeking behavior for them.…”
supporting
confidence: 60%
“…Evidence of the positive infleunce of a woman's high educational attainment on her positive contraceptive use behavior in developing countries exist (Adebayo, Gayawan, Ujuju, & Ankomah, 2013;Asekun-Olarinmoye et al, 2013;Do & Kurimoto, 2012;Ononokpono et al, 2013). By responding to non-educated women concerns through focused counselling, contraceptive misconceptions, myths and cultural norms that divest women's intention for use could be addressed.…”
Section: Addressing Women Ever and Current Contraceptive Use Concernsmentioning
confidence: 99%